2003
DOI: 10.1556/avet.51.2003.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the El Nińo phenomenon on the ovarian responsiveness and embryo production of donor cows

Abstract: The effects of different Temperature Humidity Index (THI) values in cold, hot and El Niño (EN) climates on superovulation and embryo production were analysed on Holstein Friesian donor cows. There were significant differences in the THI among the three climates. The average temperature in the EN period was 6 °C higher than in the summer period of the previous 30 years. The number of corpora lutea (CL) and embryos were log-and back-transformed, KolmogorovSmirnoff test was used for normality and Lilliefors test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…7¡4 . 0) (Be´nyei et al 2003). It has also been demonstrated that this level of THI significantly reduced the number of ovulation and the oocyte quality in superovulation cows (Be´nyei et al 2003).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…7¡4 . 0) (Be´nyei et al 2003). It has also been demonstrated that this level of THI significantly reduced the number of ovulation and the oocyte quality in superovulation cows (Be´nyei et al 2003).…”
Section: Discussionmentioning
confidence: 93%
“…In beef cattle, it has been shown that increasing environmental temperature and relative humidity from 21 xC and 35 % to 33-37 xC and 27 or 38 % during days 8 to 16 of gestation reduced the size and weight of the conceptus (Biggers et al 1987). Be´nyei et al (2003) demonstrated that the average number of corpus luteum of superovulation cows decreased from 9 . 8 to 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these reasons is the direct effect of elevated temperature on follicular development and oocyte competence [26]. In addition, HS negatively affects the superovulation response of cows and subsequently recovered embryos number, and quality [27]. A recent study on pigs reported that gilts exposed to HS during the follicular phase showed a clear induction of ovarian autophagy, and that HS increases anti-apoptotic signaling in oocytes and early follicles [28].…”
Section: Heat Stress and Altered Maternal Nutrition Impair Reproductimentioning
confidence: 99%
“…However, several studies elucidated this effect from different prospective. Based on the gene expression patterns, it has been reported that HS stimulates the apoptosis signaling pathway in oocyte by upregulation of BAX and ITM2B (apoptotic genes) [27] and in early stage embryo by down-regulate genes associated with embryonic survival, such as CDX2, a transcription factor involved in the regulation of embryo implantation and placental development [41]. In another studies, expression of growth/differentiation factor-9 (GDF9) associated with oocyte maturation was downregulated when oocyte was exposed to HS both in vivo [42] and in vitro [43].…”
Section: Heat Stress and Altered Maternal Nutrition Impair Reproductimentioning
confidence: 99%